Heart failure diagnosis and treatment – clinical aspects - Rywik, Tomasz M. (Lekarz POZ, 2018)
Heart failure is complex clinical syndrome characterized by a heterogeneous clinical picture. Heart failure diagnosis should follow the diagnostic algorithm proposed in the guidelines. However, echocardiography remains the fundamental diagnostic test finally verifying the heart failure diagnosis. At present there are three forms of heart failure stratified by ejection fraction: heart failure with reduced ejection fraction (HFrEF), heart failure with preserved ejection fraction (HFpEF), and an intermediate form, heart failure with mid-range ejection fraction (HFmrEF). We have well-established guidelines for the management of heart failure with reduced ejection fraction, which prolong survival and improve comfort of life. On the other hand, management of other forms of heart failure is mainly based on the prevention and treatment of comorbidities.